The Effect of Tax Socialization, Tax Knowledge and Taxpayer Awareness with Tax Sanctions as a Moderation Variable on Individual Taxpayer Compliance (Empirical Study on Taxpayers Registered at KPP Pratama Cibinong West Java) - Abbas Abdul Rachman Assegaf; Ronny Andesto (Jurnal Multidisiplin Madani, 2023)
Tax Socialization's Impact An empirical study on taxpayers enrolled at the Cibinong Pratama Tax Service Office in West Java examined the relationship between tax knowledge, taxpayer awareness, and tax sanctions as moderating factors on individual taxpayer compliance (supervised by Dr Ronny Andesto, SE, MM). At KPP Pratama Cibinong in West Java, this study aims to ascertain the impact of Tax Socialization, Tax Knowledge, and Taxpayer Awareness with Tax Sanctions as a moderating variable. 130 individual taxpayers registered at KPP Pratama Cibinong in West Java received questionnaires distributing the primary data. Between February and April 2020, the survey was carried out. The Partial Least Square (PLS) software was used to analyze the data. The study's findings indicate that tax socialization has a significant positive impact on individual taxpayer compliance, tax knowledge has a significant positive impact on individual taxpayer compliance, and tax payer awareness has no significant positive impact. Socialization of taxation moderated by sanctions has no significant impact on compliance with individual taxpayers, and knowledge of tax moderated by sanctions has no significant impact either